RESULTS OF CLINICAL AUDITS APPLIED IN UROLOGY PRACTICE: SYSTEMATIC REVIEW FROM 2008 TO 2023 - Taras Gutor; Andriy Zimenkovsky (Acta Medica Leopoliensia)
Aim. Identifying and evaluating the possibilities of clinical audit as exemplified by its use in urology.